Пріоритетні проблеми роботи митних органів України в умовах європейської та євроатлантичної інтеграції - Юринець, О. В.; Yurynets, O. V. (Видавництво Львівської політехніки, 2021)
Обґрунтовано актуальність та нагальність вирішення пріоритетних проблем у роботі митних органів України задля активізації процесів європейської та євроатлантичної інтеграції. Ідентифіковано та комплексно досліджено проблеми, які існують у митній сфері, за національним та міжнародним вимірами. Доведено невідкладність ліквідації митних перешкод під час здійснення експортно-імпортної діяльності в умовах європейської та євроатлантичної інтеграції за допомогою аналогового порівняння параметрів роботи вітчизняних та зарубіжних митних органів. На підставі одержаних результатів окреслено пріоритетні напрями удосконалення митних процедур задля активізації євроінтеграційних процесів.

Today, more and more companies focus on problems in customs clearance of products crossing the border during the implementation of export-import activities. In the context of European and Euro-Atlantic integration, which promote the accession of Ukrainian enterprises to the single European market, one of the priority tasks is the urgent solution of existing problems in the customs sphere. After all, one of the integral stages of Ukraine’s economic integration into the European Union is the successful accession of customs authorities to the Customs Union through harmonization of customs procedures with European norms, introduction of common customs principles and permanent improvement of customs activities on the basis of progressive customs instruments. The results of the survey of domestic exporters and importers that was conducted by the Institute for Economic Research and Policy Consulting indicated the following key problems in the work of Ukrainian customs authorities: insufficient quality of customs legislation; low level of transparency and openness of customs authorities; corruption and bribery among customs officers; intentional overstatement of the customs value of goods; low level of quality of technical support of customs authorities; low level of qualification of customs officers; frequent changes in the organizational management structure of customs authorities and their management; burdensome fiscal function of customs authorities. The identified problems in the work of customs authorities of Ukraine in the context of European and Euro-Atlantic integration made it possible to identify priority directions for improving customs procedures: increasing efficiency, transparency and non-discrimination of customs procedures for export-import operations, reducing the cost of customs clearance for export-import, absolute harmonization of domestic customs legislation with European norms, unification of customs procedures with European customs practices in export-import operations, reduction of bureaucracy of customs procedures in export-import operations, optimization of customs payments in export-import operations, etc. The implementation of these directions of improvement of customs procedures in the export-import operations should take place with the use of specific urgent customs instruments, which will promptly solve the existing urgent problems in the work of customs authorities.
Priority problems of the work of Ukrainian customs authorities in the terms of European and Euro-Atlantic integration
Keywords: митні органи; митні процедури; експортні операції; імпортні операції; проблеми; спрощення; європейська інтеграція; євроатлантична інтеграція; customs authorities; customs procedures; export operations; import operations; problems; simplifications; European integration; Euro-Atlantic integration; 339.5